2020
DOI: 10.1080/14786451.2020.1781852
|View full text |Cite
|
Sign up to set email alerts
|

Social acceptability of using low carbon building: a survey exploration

Abstract: Enhancement of buildings energy efficiency has typically been approached by viewing the buildings from a social acceptance perspective focusing on multi-level stakeholders. In order to examine social acceptance in terms of public's opinion and knowledge about using low carbon buildings, a multiple-choice questionnaire was designed with four groups of questions: background information, community perspective, social perspective, and market perspective. The study showed that 59.72% of the seventy respondents' opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It highlights that the architects, HVAC engineers, and property owners are the ones who consider the most usage of UN sustainable goals. This justifies the results from Q7 (where architects indicate the importance of embodied carbon in the material), as the building materials can contribute significantly to the achievement of UN goals [51]. The results presented in this research [52] proved that building materials can contribute significantly to the achievement of the 13 goals and 25 targets of the SDGs.…”
Section: Usage Of the Un Sustainable Goals In Your Worksupporting
confidence: 84%
See 1 more Smart Citation
“…It highlights that the architects, HVAC engineers, and property owners are the ones who consider the most usage of UN sustainable goals. This justifies the results from Q7 (where architects indicate the importance of embodied carbon in the material), as the building materials can contribute significantly to the achievement of UN goals [51]. The results presented in this research [52] proved that building materials can contribute significantly to the achievement of the 13 goals and 25 targets of the SDGs.…”
Section: Usage Of the Un Sustainable Goals In Your Worksupporting
confidence: 84%
“…However, property owners, facilities managers, construction design engineers, builders, and contractors ranked the usage of renewable energies as rather unimportant. Nevertheless, when it comes to the knowledge of energy efficiency, the survey [51] highlighted that most of the respondents consider renewable energy technologies (RETs) such as solar PV as one the energy-efficiency options among others such as solar hot water, nuclear power, power plant, wind energy, solar power plants, etc.…”
Section: Importance Of Carbon Neutrality Reaching the Nzebmentioning
confidence: 99%
“…To ensure end-user participation, the real estate housing market must introduce financial incentives to buy low-carbon buildings [93]. The study found that the public is willing to learn more about renewable resource knowledge and hoped that the government could take corresponding measures to raise awareness of low-carbon buildings [94]. Countries should take the government's lead to publicize the advantages and benefits of low-carbon buildings, advocate a low-carbon lifestyle, enhance the awareness of low-carbon buildings, and thus increase the market demand for low-carbon buildings.…”
Section: Discussionmentioning
confidence: 99%
“…This learning ability as a feature of intelligent construction needs to account for the influence of factors like human and AI agent responsibilities, as well as training environment characteristics, on the learning procedure in dynamic, uncertain environments. [17]. Furthermore, there is a lack of research that details the training of autonomous, building-integrated AI systems with the ability to make autonomous decisions [18].…”
Section: Introductionmentioning
confidence: 99%